Crystal structure of cis-(1,4,8,11-tetraazacyclotetradecane-κ4N)bis(thiocyanato-κN)chromium(III) bromide from synchrotron X-ray diffraction data - Dohyun Moon (Acta Crystallographica Section E: Crystallographic Communications, 2021)
The crystal structure of the title complex, cis-[Cr(NCS)2(cyclam)]Br (cyclam = 1,4,8,11-tetraazacyclotetradecane, C10H24N4), has been determined from synchrotron X-ray data. The asymmetric unit contains one [Cr(NCS)2(cyclam)]+ cation and one bromide anion. The CrIII ion of the complex cation is coordinated by the four N atoms of the cyclam ligand and by two N-coordinating NCS groups in a cis arrangement, displaying a distorted octahedral coordination sphere. The Cr—N(cyclam) bond lengths are in the range 2.075 (3) to 2.081 (3) Å while the average Cr—N(NCS) bond length is 1.996 (16) Å. The macrocyclic cyclam moiety adopts the most stable cis-V conformation. The crystal structure is stabilized by intermolecular hydrogen bonds involving the cyclam N—H groups as donor groups, and the bromide anion and the S atom of one of the NCS ligands as acceptor groups.